Depletion of HPV16 early genes induces autophagy and senescence in a cervical carcinogenesis model, regardless of viral physical state. Issue 3 (9th October 2013) - Hanning, Jennifer E; Saini, Harpreet K; Murray, Matthew J; Caffarel, Maria M; van Dongen, Stijn; Ward, Dawn; Barker, Emily M; Scarpini, Cinzia G; Groves, Ian J; Stanley, Margaret A; Enright, Anton J; Pett, Mark R; et al.
Abstract In cervical carcinomas, high‐risk human papillomavirus (HR‐HPV) may be integrated into host chromosomes or remain extra‐chromosomal (episomal). We used the W12 cervical keratinocyte model to investigate the effects of HPV16 early gene depletion on in vitro cervical carcinogenesis pathways, particularly effects shared by cells with episomal versus integrated HPV16 DNA. Importantly, we were able to study the specific cellular consequences of viral gene depletion by using short interfering RNAs known not to cause phenotypic or transcriptional off‐target effects in keratinocytes. We found that while cervical neoplastic progression in vitro was characterized by dynamic changes in HPV16 transcript levels, viral early gene expression was required for cell survival at all stages of carcinogenesis, regardless of viral physical state, levels of early gene expression or histology in organotypic tissue culture. Moreover, HPV16 early gene depletion induced changes in host gene expression that were common to both episome‐containing and integrant‐containing cells. In particular, we observed up‐regulation of autophagy genes, associated with enrichment of senescence and innate immune‐response pathways, including the senescence‐associated secretory phenotype (SASP). In keeping with these observations, HPV16 early gene depletion induced autophagy in both episome‐containing and integrant‐containing W12 cells, as evidenced by the appearance of autophagosomes, punctate expression of the autophagy marker LC3, conversion of LC3B‐I to LC3B‐II, and reduced levels of the autophagy substrate p62. Consistent with the reported association between autophagy and senescence pathways, HPV16 early gene depletion induced expression of the senescence marker beta‐galactosidase and increased secretion of the SASP‐related protein IGFBP3. Together, these data indicate that depleting HR‐HPV early genes would be of potential therapeutic benefit in all cervical carcinogenesis pathways, regardless of viral physical state. In addition, the senescence/SASP response associated with autophagy induction may promote beneficial immune effects in bystander cells. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.